Chemical composition of Achatina fulica - Aboua, F. (Tropicultura, 1990)
Proximate composition and mineral content were determined in snail without and with shell and shell atone from Achatina fulica. This snail has high protein (above 40 %), low fat (less than 3 %) and is a relatively good source of macrominerals, including calcium, phosphorus, magnesium, potassium and sodium. Achatina fulica is an excellent source of iron but is poor in copper, zinc and manganese. The snail is very rich in calcium but very poor in phosphorus, potassium and magnesium.